Evaluation of Collagen Membranes Coated with Testosterone and Alendronate to Improve Guided Bone Regeneration in Mandibular Bone Defects in Minipigs - Bart A. J. A. van Oirschot (eJournal of Oral Maxillofacial Research, 2020)
Objectives: The purpose of the present in vivo study was to evaluate whether pericard collagen membranes coated with ancillary amounts of testosterone and alendronate in a poly-lactic glycolic acid (PLGA) carrier as compared to uncoated membranes will improve early bone regeneration.